Analysis of Maintenance and Repair of the Toyota Rush Automatic Transmission at Tunas Toyota Tangerang - Prasetyo, Bagas Aji; Abdillah, Hamid (The Future of Education Journal, 2025)
The transmission is a component that functions to convert the driving energy and speed from the engine into varying torque and speed, which is then transferred to the final drive. This change affects the rotational speed, which may be reduced from a previously higher speed with greater power, or vice versa, in order to transmit engine power to the drive wheels. The system also requires three shafts, one of which is the input shaft. This component is directly connected to the clutch. The input shaft serves as a channel for engine power from the clutch to be transmitted to the countershaft gears. The countershaft is responsible for transferring power within the transmission system to the final gear. These components also serve as mounting points for the vehicle's gear shifter. Shafts function to deliver torque from the transmission system to the final gear components. This study aims to examine the maintenance and repair procedures of the clutch system, including clutch plate replacement and automatic transmission fluid (ATF) change, specifically in the Toyota Rush vehicle.